Case Report: Viral Pneumonia Could Prompt the Advancement of Immune-Mediated Liver Disease - Li, Qian; Wang, Jun; Zhou, Xueshi; Lu, Hongzhou; Lu, Mengji; Huang, Lihua (Frontiers in Medicine, 2021)
Background The impact of the influenza A (H1N1) and SARS-CoV-2 virus on the development of autoimmune hepatitis has not been described previously. Methods In this case series, we evaluated the dynamic changes in liver function of three patients with autoimmune hepatitis who presented with viral infection (two with the H1N1 and one with the SARS-CoV-2 virus) during the recent COVID-19 outbreak. Result Patient 1 was a 68-year-old woman with a history of hepatitis of unknown origin before being infected with the H1N1 virus. Autoimmune hepatitis with an exacerbation of liver injury was diagnosed during the infection. Patient 2 was a 48-year-old woman with pre-existing autoimmune hepatitis. Despite being on immunosuppressant therapy (using glucocorticoids), liver injury recurred with elevated total bilirubin and gamma-glutamyl transferase levels post H1N1 infection. Patient 3 was a 61-year-old woman with probable autoimmune hepatitis. Liver injury recurred with a flare in alanine transaminase/aspartate transaminase levels post SARS-CoV-2 infection, in spite of the patient being on liver protection therapy (using ursodeoxycholic acid). Conclusion The case series raises the possibility that COVID-19 or influenza induced pneumonia triggers the progression of autoimmune hepatitis.